Preschool: The Contribution of Economic Tokens in Autonomy - Sholichah, Ima Fitri; Hapsari, Indria Galuh (Universitas Negeri Surabaya, 2025)
Background: The problem of autonomy experienced by preschool-aged children is that they do not fully have autonomy, such as students being assisted by teachers and parents when carrying out learning activities. Objective: An economic tokens contribution in increasing student’s autonomy. Method: This study used an experimental method with a one-group pretest-posttest design. Partisipan used 10 students of Kindergarten grade A. Data collection used the Autonomy Scale. Analysis of the results of the study using the gain score and the Wilcoxon test. Results: The study showed that there was a contribution of the economic tokens in increasing autonomy. In the beginning, before the economic tokens was implemented, students were somewhat less autonomy and too dependent on the people around them while studying. After implementing economic tokens in teaching and learning process, students experience changes, namely being more autonomy in the learning process in class. Conclusion: The economic tokens is attractive to students because students are eager to learn and feel like trying to learn with rewards after students are able or successful in carrying out the expected behavior. Keywords: Autonomy; economic tokens; preschool; student. Abstrak Latar Belakang: Permasalahan kemandirian yang dialami anak usia prasekolah yaitu belum sepenuhnya memiliki kemandirian dalam aktivitas belajar seperti siswa masih dibantu oleh guru dan orang tua saat melakukan kegiatan belajar, telat merespon stimulus guru serta siswa belum bisa mematuhi tata terbit kelas sehingga kelas menjadi tidak kondusif. Tujuan: Penelitian ini bertujuan untuk mengetahui kontribusi token ekonomi dalam meningkatkan kemandirian siswa. Metode: Penelitian menggunakan metode eksperimen dengan one group pretest-posttest design. Partisipan berjumlah 10 siswa. Pengumpulan data menggunakan Skala Kemandirian. Analisis hasil penelitian menggunakan gain score dan uji Wilcoxon. Hasil: Hasil penelitian menunjukkan adanya kontribusi token ekonomi dalam meningkatkan kemandirian siswa Taman Kanak-kanak kelas A. Pada awal sebelum dilakukan metode token ekonomi siswa masih bergantung pada orang-orang di sekitarnya saat belajar. Setelah diimplementasikan token ekonomi, siswa mengalami perubahan lebih mandiri dalam proses belajar di kelas. Simpulan: Metode token ekonomi merupakan metode yang menarik bagi siswa karena metode ini membuat siswa semangat dalam belajar dan rasa ingin berusaha dalam belajar. Dengan adanya reward, siswa menunjukkan perilaku yang diharapkan ketika siswa mampu atau berhasil melakukan instruksi yang diberikan. Kata Kunci: Anak usia dini; kemandirian; siswa; token ekonomi.